2019
DOI: 10.1016/j.nicl.2019.101815
|View full text |Cite
|
Sign up to set email alerts
|

Visual input drives increased occipital responsiveness and harmonized oscillations in multiple cortical areas in migraineurs

Abstract: Migraineurs are hypersensitive for most sensory domains like visual, auditory or somatosensory processing even outside of attacks. This behavioral peculiarity is mirrored by findings of cortical hyper-responsivity already in the interictal state. Using repetitive visual stimulation to elicit steady state visually evoked potentials (SSVEP) in 30 interictal episodic migraineurs and 30 controls we show hyper-responsivity of the visual cortex in the migraineurs. Additionally, the occipital regions were remarkably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 63 publications
5
21
0
Order By: Relevance
“…The correlation analysis also showed that both the MEP and the SSEP slope increase with the time elapsed since the last attack increases. Comparable switches depending on the phase of the migraine cycle have been reported for a number of brain studies in migraine: resting MEP threshold [7], visual cortex responsivity [32][33][34], lateral inhibition of the visual [32] and somatosensory [20] cortices, spinal trigeminal nucleus activation [35], brainstem serotonergic receptor binding [36] and thalamic microstructure [37]. All these studies support the concept that the recurrence of migraine attacks is associated with cycling functional and morphological alterations in cortical and subcortical centers.…”
Section: Discussionsupporting
confidence: 70%
“…The correlation analysis also showed that both the MEP and the SSEP slope increase with the time elapsed since the last attack increases. Comparable switches depending on the phase of the migraine cycle have been reported for a number of brain studies in migraine: resting MEP threshold [7], visual cortex responsivity [32][33][34], lateral inhibition of the visual [32] and somatosensory [20] cortices, spinal trigeminal nucleus activation [35], brainstem serotonergic receptor binding [36] and thalamic microstructure [37]. All these studies support the concept that the recurrence of migraine attacks is associated with cycling functional and morphological alterations in cortical and subcortical centers.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies have shown that the general time course of migraine attacks normalizes neural functioning during attack and that the abnormalities increase with longer time since attack. [50][51][52][53][54][55][56][57][58] Therefore, not controlling for time since attack may have introduced more noise into the data, reducing the effect of color on visual discomfort in migraine (and the effect might have been even stronger than we have demonstrated). For future studies, careful monitoring of days since or until next migraine attack ought to be recorded.…”
Section: Large and Large Chromaticity Separations For Individuals Wimentioning
confidence: 76%
“…Notably, migraine and migraine-induced symptoms have a strong association with anxiety and depression [2]. Additional network circuits have been implicated in migraine pathophysiology and other types of negative emotional and affective processes, including the thalamo-cortical system, based on evidence for altered microstructures and functional connectivities [18]. Nevertheless, few of the currently available studies have specifically revealed abnormal thalamic FC with the visual network and correlations with neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%